Ecological contexts and youth civic and political engagement in Paris, France - Allen, LaRue; Bang, Hee Jin (Journal of Applied Developmental Psychology, 2015)
With high rates of migration worldwide in the past decade, industrialized nations have witnessed substantial growth in the diversity of their populations and challenges to the civic and political status quo. This paper focuses on France, among the top countries sought by immigrants. Survey data were collected from 632 students from four ethnically diverse high schools in the Paris region, of whom 362 were between ages 14 and 17. We examine patterns of anticipated involvement in three indices of political and civic engagement, with the goal of identifying the characteristics that significantly contribute to explaining each. Results showed that most demographic characteristics are relatively weak in explaining the outcomes. Knowledge and attitudes developed in school, along with the effects of contact with family, peers, and more distal contexts, are important antecedents of political and civic engagement, although the magnitude of the effects differs for males and females.
Keywords: Civic engagement; French youth; Gender differences; Political participation